2009
DOI: 10.1194/jlr.r800051-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of lipid species by MALDI mass spectrometry

Abstract: Recent developments in MALDI have enabled direct detection of lipids as intact molecular species present within cellular membranes. Abundant lipid-related ions are produced from the direct analysis of thin tissue slices when sequential spectra are acquired across a tissue surface that has been coated with a MALDI matrix. The lipid-derived ions can often be distinguished from other biomolecules because of the significant mass defect that these ions present due to the large number of covalently bound hydrogen at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
245
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(253 citation statements)
references
References 18 publications
6
245
1
1
Order By: Relevance
“…The FA detected and here described as masses specific to the OA condition, could be part of these lipids. Future parallel studies using MALDI-imaging for instance, could discriminate these intact lipids as other authors have shown (33)(34)(35).…”
Section: Pca Revealed the Presence Of Droplets Rich In Lipids In Oa Cmentioning
confidence: 94%
“…The FA detected and here described as masses specific to the OA condition, could be part of these lipids. Future parallel studies using MALDI-imaging for instance, could discriminate these intact lipids as other authors have shown (33)(34)(35).…”
Section: Pca Revealed the Presence Of Droplets Rich In Lipids In Oa Cmentioning
confidence: 94%
“…A significant advantage of imaging MS is acquiring chemical information in situ. However, significant tissue preparation is often required that can adversely affect quantitative accuracy and compositional distribution (23). For example, the quantitative accuracy of MALDI-MS and TOF-SIMS is significantly affected by sample preparation necessary to withstand vacuum pressure and ion generation energies (25).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipids are the most abundant lipid constituents, are widely distributed in the brain, and are readily ionized and detected in MALDI MS experiments. Several studies have already reported the distribution of the commonly known phospholipids within the anatomical regions of the brain in fresh tissue sections [16,20,22,24,46,47,51,[54][55][56][71][72][73].…”
Section: Introductionmentioning
confidence: 99%